ANALISIS HUKUM PEMANFAATAN SUMBER DAYA AIR UNTUK KEBUTUHAN RUMAH PENDUDUK DALAM PERSPEKTIF KESEJAHTERAAN - Husein, Saddam; Nuraeny, Henny (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Water is a natural resource that is very important in everyday life. Some of the benefits of water resources in daily life include irrigation in agriculture, electricity generation, and household activities. The problem that arises is whether the regulation and use of water resources is in accordance with the needs of residents’ homes, and how are sanctions applied for misuse of water resources that are not in accordance with the intended needs of residents’ homes? The aim of this research is to find out and analyze the use of water resources for residents’ housing needs, and to provide alternative solutions to the application of sanctions for misuse of water resources that are not in accordance with the intended use of residents’ housing needs. The research method used is normative juridical, with a legislative approach as primary legal material combined with observation and observation as secondary legal material, especially a welfare perspective. results: That the use of water resources for daily needs is not yet optimal, even though there have been several statutory regulations, therefore the implementation of water quality protection and management should be carried out through a process of planning, utilization, control and maintenance, so that the need for water resources for people’s homes are filled. That the alternative solution is to enforce the law firmly and clearly and strictly supervise perpetrators who commit violations against the use of water resources for the needs of residents’ homes.